2016
DOI: 10.1103/physrevb.93.235407
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of ultrasharp trapped-mode resonances in mirror-symmetric metamaterials

Abstract: We experimentally demonstrate a metamaterial structure composed of two mirror-symmetric joint split ring resonators (JSRRs) that support extremely sharp trapped-mode resonance with a large modulation depth in the terahertz region. Contrary to the regular mirror-arranged SRR arrays in which both the subradiant inductivecapacitive (LC) resonance and quadrupole-mode resonance can be excited, our designed structure features a metallic microstrip bridging the adjacent SRRs, which leads to the emergence of an otherw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 43 publications
0
43
0
1
Order By: Relevance
“…As a result, the effective area and efficiency for ultra‐sub‐wavelength strong light‐matter interactions are also very limited and thus, conventional Fano metamaterial devices are limited for practical device applications. Recently, people have tried to implement trapped mode in mirror‐symmetric metamaterials . However, such structures have lower field confinement, lossy, and show low Q resonances.…”
mentioning
confidence: 99%
“…As a result, the effective area and efficiency for ultra‐sub‐wavelength strong light‐matter interactions are also very limited and thus, conventional Fano metamaterial devices are limited for practical device applications. Recently, people have tried to implement trapped mode in mirror‐symmetric metamaterials . However, such structures have lower field confinement, lossy, and show low Q resonances.…”
mentioning
confidence: 99%
“…The slight discrepancies in resonant frequencies and shallower depth of the resonances are possibly attributed to the fabrication tolerances. As shown in Figure c, two pronounced plasmonic resonances are clearly observed for both LCP and RCP incidence light at 44 and 72 THz, respectively, which is associated with the excitation of the fundamental modes in the eta‐shaped metasurface . The unfolded metasurface provides the expected nearly identical transmission of LCP and RCP light, which implies that there is no intrinsic chirality in the eta‐shaped metasurface.…”
mentioning
confidence: 92%
“…In the case of unfolded metasurface, the metasurface strongly couples with both LCP and RCP incident light, and its transmission property is featured by double broadband resonances (see Figure c,e). For the lower frequency resonance occurring at around 43 THz, circular electric current distribution is excited in the eta‐shaped metasurface leading to out‐of‐plane magnetic and in‐plane electric dipole excitation, as illustrated in Figure a, which corresponds to the lowest even eigenmode of the structure . However, for the higher frequency resonance occurring at around 73 THz, the surface currents are split into two oscillation modes and characterized by the presence of a node in the entire structure, as shown in Figure b.…”
mentioning
confidence: 98%
“…The magnetic resonance of the AS-RRs can be excited by electromagnetic wave with polarization direction perpendicular to the gap of the ASRRs. The near-field coupling [23,[46][47][48][49] of these magnetic resonators will induce a toroidal moment dominated fundamental resonance in the planar metamaterial. In the study, it is found that the excitation of toroidal mode in a metamaterial can be significantly enhanced, and in the meanwhile, the Q-factor of the planar metamaterial can be further improved through the control of toroidal excitations.…”
Section: Introductionmentioning
confidence: 99%